2019
DOI: 10.1111/aej.12378
|View full text |Cite
|
Sign up to set email alerts
|

Cone‐beam computed tomography accuracy in pulp chamber size evaluation: An ex vivo study

Abstract: This study aimed to assess ex vivo the accuracy of cone-beam computed tomography (CBCT), as compared to operative microscope, for evaluating pulp chamber size. A total of forty teeth were extracted for periodontal reasons and a horizontal section was done at the most apical level of the cement-enamel junction. The pulp chamber was photographed using a digital camera connected to an optical microscope. Then, the tooth was scanned with CBCT and the horizontal slide matching the anatomical section of pulp chamber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Figure 9 shows the results of multiple watershed algorithm [ 6 ], Chan–Vese segmentation algorithm [ 25 ], graph cut segmentation algorithm [ 3 ], and the algorithm in this paper on the test set. It shows that the neural network model has a well effect in image segmentation.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 9 shows the results of multiple watershed algorithm [ 6 ], Chan–Vese segmentation algorithm [ 25 ], graph cut segmentation algorithm [ 3 ], and the algorithm in this paper on the test set. It shows that the neural network model has a well effect in image segmentation.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…For example, both CT and MRI images give anatomical information of target, but MRI is better at distinguishing soft tissues with similar densities such as gray matter and white matter in the brain tissue. CT images are better in areas with large differences in the density of bone tissues [ 5 , 6 ]. Nevertheless, the continuous two-dimensional slice image set provided by these devices can only intuitively receive certain section information of a certain part of the organ, and it is easy to get tired.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to equine hypsodont teeth, a common pulp chamber is placed in the crown region in the brachydont teeth of humans, which gives rise to pulp canals in the apical direction [14,16]. Using cone-beam computed tomography (CBCT), the dimensions of the pulp chamber have been determined in human teeth [33,34]. The pulp chambers in young human teeth feature cross-sectional diameters of up to 10 mm 2 .…”
Section: Morphology: Age-related Changes In the Equine Dental Pulpmentioning
confidence: 99%
“…Detailed knowledge of the spatial dimensions and architecture of the pulp compartments is of central importance for modern endodontic treatment approaches in human dental medicine. Therefore, it has been recommended to display the three-dimensional anatomy of the pulp systemthrough the use of cone-beam computed tomography prior to endodontic treatment [34,36,37].…”
Section: Morphology: Age-related Changes In the Equine Dental Pulpmentioning
confidence: 99%
“…In the last years, it has been reported the use CBCT to determine the volume of the dental pulp chamber but, as far as we know, studies corroborating its accuracy and reproducibility are not available. Thus, this study was designed to validate the precision CBCT by comparing pulp chamber volume measurements ex vivo obtained with Promax ® 3D Max CBCT and those obtained with micro-CT. A recent study by Maddalone et al [26] concluded that CBCT is suitable for pulp chamber morphology evaluation with limitations in detecting the anatomical variability of small branches in root canal system.…”
Section: Introductionmentioning
confidence: 99%